The Indonesian Electronic Information and Transactions Within Indonesia's Broader Legal Regime: Urgency for Amendment? - Tasya Safiranita; Travis Tio Pratama Waluyo; Elizabeth Calista; Danielle Putri Ratu; Ahmad M. Ramli (Jurnal HAM, 2021)
Cyberspace is the interdependent network of information technology infrastructures such as the internet, telecommunications networks, and computer systems. Meanwhile, Indonesia's Law Number 11 of 2008 and its amendment through Indonesian Law Number 19 of 2016 governing cyberspace have been viewed to contradict and infringe other areas of law, such as protection of press or freedom of expression. Hence, this study seeks to identify the controversies and problems regarding the law deemed urgent for amendment. Further, this study creates recommendations so the government may amend electronic information policy more fairly and efficiently. This study uses a judicial normative and comparative approach. This research tries to analyze the existing regulations and the implementation and compare Indonesia's cyberspace regulation with other States'. This study finds that Articles 27(3) and 28(2) of the law criminalize defamation and hate speech in an overly broad manner and that Article 40(2)(b) allows the government to exercise problematic censorship. As a result, they have infringed the freedom of the press and general freedom of expression in practice. In response to this, this study compares similar provisions from other States and recommends amendment the articles to become narrower and more clearly defined.